ASPEK PERLINDUNGAN HUKUM TERHADAP PEMBELI DALAM MELAKUKAN TRANSAKSI JUAL BELI MELALUI ELECTRONIC COMMERCE (Studi Kasus Putusan Pengadilan Nomor 183/Pdt.G/2018/PN.Mdn) - Warsifah, Warsifah; Gurion Napitupulu, David (IBLAM LAW REVIEW, 2022)
The development of technological advances, especially in the development of the internet in Indonesia, apparently also affects business development and the way of transacting in buying and selling transactions through electronic commerce. The use of the internet through e-commerce provides convenience, time efficiency, convenience and so on. Buying and selling transactions through e-commerce are basically the same as conventional buying and selling transactions, but what makes the difference is the media where buyers and sellers meet in buying and selling transactions, namely through the use of the internet in cyberspace. The e-commerce sale and purchase transaction, in the agreement is also the same as the conventional sale and purchase transaction, on the condition that the agreement written in Article 1320 of the Civil Code and the agreed agreement is made in the form of an electronic contract. Often in buying and selling transactions through e-commerce, the party who is harmed is the consumer as the buyer with the contents of the previously agreed agreement not being implemented properly by the seller. These violations range from defaults to consumer disputes. By studying and analyzing case studies in the results of court decisions number 183/Pdt.G/2018/PN.Mdn, it aims to find out the judge's considerations and the legal relationship between the buyer as the Plaintiff and the Defendant and to know aspects of legal protection for the buyer in making a sale transaction. buy through e-commerce.